2009
DOI: 10.1249/mss.0b013e3181949333
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Physical Activity Intervention Strategies for Weight Loss and Prevention of Weight Regain for Adults

Abstract: Overweight and obesity affects more than 66% of the adult population and is associated with a variety of chronic diseases. Weight reduction reduces health risks associated with chronic diseases and is therefore encouraged by major health agencies. Guidelines of the National Heart, Lung, and Blood Institute (NHLBI) encourage a 10% reduction in weight, although considerable literature indicates reduction in health risk with 3% to 5% reduction in weight. Physical activity (PA) is recommended as a component of wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

53
1,642
14
144

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 2,166 publications
(1,853 citation statements)
references
References 144 publications
53
1,642
14
144
Order By: Relevance
“…Several studies have reported indications for obtaining the direct effect of exercise on hepatic steatosis [6][7][8] ; exercise with less frequency and dose was found to be effective in both light and moderate volume exercise programs, 34 the PA volume of which was below the current guidelines for health promotion 35 and for managing body weight. 36 At present, scientific evidence for the benefits of PA and the optimal dose and modality for PA in NAFLD management is limited. 11 In summary, the results of this study show the beneficial effects of increasing the volume of MVPA combined with dietary restriction on managing NAFLD in obese, middle-aged men.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported indications for obtaining the direct effect of exercise on hepatic steatosis [6][7][8] ; exercise with less frequency and dose was found to be effective in both light and moderate volume exercise programs, 34 the PA volume of which was below the current guidelines for health promotion 35 and for managing body weight. 36 At present, scientific evidence for the benefits of PA and the optimal dose and modality for PA in NAFLD management is limited. 11 In summary, the results of this study show the beneficial effects of increasing the volume of MVPA combined with dietary restriction on managing NAFLD in obese, middle-aged men.…”
Section: Discussionmentioning
confidence: 99%
“…The exercise program was based on guidelines from the American College of Sports Medicine. 23 Resistance training was also designed based on American College of Sports Medicine recommendations. 24 Exercises targeted each of the main muscle groups.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 Childhood activity patterns may be particularly important if they persist into adulthood. One proposed strategy involves making structural changes in the environments within which children live, 9 especially in areas where children have the greatest risk of sedentary behavior patterns, obesity, and related chronic diseases.…”
mentioning
confidence: 99%